Outcomes of Introducing Early Learners to Interprofessional Competencies in a Classroom Setting. Issue 4 (2nd October 2017) - Lockeman, Kelly S.; Lanning, Sharon K.; Dow, Alan W.; Zorek, Joseph A.; DiazGranados, Deborah; Ivey, Carole K.; Soper, Shawne
ABSTRACT: Problem : Although interprofessional practice is important for improving healthcare delivery, there is little evidence describing interprofessional education (IPE) outcomes beyond changes in attitudes and knowledge of prelicensure learners. More rigorous evaluation of early IPE is needed to determine its impact on teaching interprofessional collaborative practice and providing a solid foundation for applying collaborative skills in the clinical environment. Intervention : First-year students ( N = 679) in 7 health professions programs participated in a 4-session series focusing on professional roles and responsibilities, teams and teamwork, and the healthcare system. Interprofessional teams of 5–6 students, from at least 3 professions, were assembled for the duration of the series and created a team charter during their first session to guide their work. Each subsequent session included a brief lecture and interactive exercises. Faculty facilitators from the participating programs provided support to students during the sessions. As a culminating project, each team created a short video depicting a barrier to interprofessional collaboration. Students evaluated the performance of their team members using a web-based peer assessment survey. A course evaluation with an embedded validated attitudinal scale was used to assess changes in student perceptions about IPE. A sample of videos were also scored by 2 faculty using a rubric linked to course expectations. Context : This educational offering took place on the health sciences campus of a large, mid-Atlantic research university with more than 3, 200 clinical learners in schools of allied health professions, dentistry, medicine, nursing, and pharmacy. It was the first interprofessional activity for most of the learners. Outcome : There were 555 students who participated in some or all of the sessions. Comments indicated that students enjoyed interacting with their peers and prefer activities allowing them to apply content to their profession over lectures. The assessment measures revealed a disconnect between student ratings targeting interprofessional socialization and faculty ratings targeting the products of their teamwork. Although students provided positive feedback to their teammates through peer assessment, and the attitudinal scale showed a small but significant increase in positive attitudes toward IPE, the videos they created did not demonstrate a deep understanding of barriers to interprofessional practice. Lessons Learned : This large-scale IPE activity for early learners supported progress toward interprofessional socialization, but student learning was inconsistently demonstrated in teamwork products. Course planners should augment self- and peer-reported interprofessional socialization measures with faculty-generated behavioral outcome assessments. Such triangulation produces a more robust data set to inform decisions about curricular revisions and development.